2003
DOI: 10.1063/1.1626258
|View full text |Cite
|
Sign up to set email alerts
|

Electron drift velocity in AlGaN/GaN channel at high electric fields

Abstract: Current–voltage characteristics of a nominally undoped AlGaN/GaN two-dimensional electron gas channel is measured at a room temperature, and electron drift velocity is deduced under assumption of uniform electric field and field-independent electron density. No velocity saturation is reached at fields up to 130 kV/cm, when the effect of Joule heating is minimized through application of nanosecond pulses of voltage. The estimated drift velocity is near 2×107 cm/s at 130 kV/cm. Monte Carlo simulation of the drif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 18 publications
3
54
2
Order By: Relevance
“…In the case of the heterostructures, models were created to study the role of non-equilibrium optical phonons and how they can lower the average drift velocity. The velocity observed in the experiments of this study is incompatible with the onset of non-equilibrium phonons that has been suggested earlier to explain low observed velocities [17]. Hence, the reduction observed earlier is unlikely to be due to the onset of non-equilibrium phonons, and more likely to inhomogeneity effects, as well as poor contacts.…”
Section: Bothcontrasting
confidence: 51%
See 2 more Smart Citations
“…In the case of the heterostructures, models were created to study the role of non-equilibrium optical phonons and how they can lower the average drift velocity. The velocity observed in the experiments of this study is incompatible with the onset of non-equilibrium phonons that has been suggested earlier to explain low observed velocities [17]. Hence, the reduction observed earlier is unlikely to be due to the onset of non-equilibrium phonons, and more likely to inhomogeneity effects, as well as poor contacts.…”
Section: Bothcontrasting
confidence: 51%
“…In contrast to this, however, there are both experiments and Monte Carlo simulations which suggest that a much lower value of the velocity occurs, of the order of 1×10 7 cm/s at fields above 10 kV/cm [14,15,16]. This same group has, however, obtained a drift velocity above 2×10 7 cm/s at around 140 kV/cm [17], with essentially linear behavior at lower fields, by using short pulses. They attribute the lower values observed earlier to carrier heating.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The obtained value of the activation energy practically coincides with the energy of the LO phonons in GaN, 92 meV, which was deduced from hot carrier transport experiments. 7,9 About the same phonon energy of 91 meV was obtained from optical measurements. 10 The coincidence of the activation energy extracted from photoconductivity measurements and the LO-phonon energy seems to be unexpected.…”
Section: ͑2͒mentioning
confidence: 99%
“…6 Thus, correct measurements of this characteristic have to be done in pulse regimes. [7][8][9] Another parameter, the electron temperature, determines stochastic characteristics of the electrons, their fluctuations, and current noise. In this letter, we present experimental results on the velocity-field characteristics in AlGaN / GaN heterostructures obtained by using 10-30 ns pulse current-voltage measurements in the range of electric fields up to 150 kV/ cm.…”
mentioning
confidence: 99%